Hardiness dan Parenting Self-Efficay pada Orang Tua Anak Berkebutuhan Khusus - Rachmahana, Ratna Syifa’a (UIR Press, 2022)
This study aimed to examine the relationship between the variables of hardiness and parenting self-efficacy in parents with special needs children’s. The hypothesis in this study was there is a positive relationship between hardiness and parenting self-efficacy, the higher the hardiness variable, the higher the parenting self-efficacy variable too. The subjects in the study were 84 parents of children with special needs. Data collection uses two scales, namely the hardiness scale based on Maddi and Kobasa's hardiness construct (α = 0.725, N = 14) and the parenting self-efficacy scale based on the Coleman and Karraker construct (α = 0.896, N = 30). The result of this study is significantly positive relationship between hardiness and parenting self-efficacy, with correlation test using Pearson's product moment show the result is p = 0.000, r = 0.819.